POLITICAL IMPASSE AND UN INTERVENTION IN COTE D’IVOIRE - Kah, Henry Kam (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
In this paper we argue that the United Nations peacekeeping mission in Cote D’Ivoire contributed to the return of peace in the country but encountered enormous challenges and scathing criticisms. The mission was established in April 2004 with the aim of normalising the tense political atmosphere in a divided country where rebel forces (Forces Nouvelles) controlled Northern Cote D’Ivoire and government forces controlled the Southern part of the country. The mission was to build community security, trust in the people and institutions and protect human rights in a country torn apart by civil war. Prior to the 2002-2003 cease-fire agreement between belligerents, Cote D’Ivoire’s political terrain was heavily polluted with no agreement on almost every sticky issue. This widened regional and political cracks in the country and the despicable human rights situation re-ignited political violence. Besides, prior electoral concertation fuelled mistrust among politicians and indiscipline reigned supreme in the army threatening peace. Army commanders had soiled their hands in illicit natural resource exploitation and soldiers erected clandestine checkpoints to extort money from the population. Gender-based violence was rife and mercilessly gullible political hawks did not protect the population. Through a content analysis of essentially documents produced by the UN operations in Cote d’Ivoire (UNOCI) we conclude that it was able to navigate through numerous hurdles amidst accusations, counter accusations and virulent criticisms.